Straits settlements Laws [1902-1912] (Petaling Jaya : Arkib Negara)
Mengandungi vol. II 1901-1907 no. 102-103 (samb.) Vol. III 1908-1912 No. 104-125 termasuk ordinan-ordinan no. 102 Civil Procedure Code (Ord. no. XXXI of 1907); Ordinance no. 103 Stamps (Ord. XXXVI of 1907); Ord. no. 104 Youthful Offenders; Reception (ord. No. IX of 1908); Ord. no. 109 Petroleum (Ord. No. XXIII of 1908); Ord. no. 113 Native States Orisoners (Ord. No. X of 1909); Ord. no. 116 societies (Ord. No.XXX of 1909); Ord. no. 119 Hospitals Board (Ord. No. V of 1910); Ord. No. 121 Criminal Procedure Code (Ord. No. X of 1910; Ord. No. XII of 1905); Ord. no. 123 Divorce (Ord. No. XXV of 1910).